High-performance flexible ZnO nanorod UV photodetectors with a network-structured Cu nanowire electrode. Issue 37 (12th September 2016) - Kwon, Do-Kyun; Lee, Su Jeong; Myoung, Jae-Min
Abstract : By using network-structured Cu NW electrodes, UV photodetectors showed improved sensing properties and high flexibility. Abstract : In this work, vertically aligned zinc oxide (ZnO) nanorod (NR)-based flexible ultraviolet (UV) photodetectors were successfully fabricated on a polyimide (PI) substrate with a copper (Cu) nanowire (NW) electrode. To enhance the flexibility and sensing properties, the entangled networks of Cu NWs were applied to UV photodetectors as a flexible electrode. Here, Cu NWs have a high conductivity with a low cost compared to other metals to achieve a Schottky contact with ZnO NRs. Moreover, because of forming a network structure, the surface of the sensing material has a large contact area with oxygen molecules, resulting in a faster response time. The Cu NW electrode exhibited a high optical transmittance of 90%, a considerable sheet resistance of 50 Ω sq −1, and a work function of 5.12 eV. Consequentially, the fabricated UV photodetector with Cu NW electrodes showed excellent UV sensing properties with a very fast rising time of 0.7 s and a decay time of 1.9 s in the dark and under UV illumination (365 nm, 0.40 mW cm −2 ) at a reverse bias of −2.0 V. Furthermore, during the bending test at a radius of curvature of 5 mm, the flexible ZnO NR UV photodetectors with Cu NW electrodes exhibited almost unchanged UV sensing properties even after 5000 cycles.